A hybrid and dynamic reliable transport protocol for wireless sensor networks. (November 2015) - Sharma, Bhisham; Aseri, Trilok C.
Graphical abstract: Highlights: A hybrid and dynamic reliable transport protocol for wireless sensor networks is proposed. It provides hybrid Acknowledgement/Negative Acknowledgement scheme. It controls the booting sensor nodes problem and the all-packets-lost problem. The performance of proposed protocol is tested under TinyOS Simulator. Abstract: Wireless sensor networks are formed by a large number of sensor nodes which are commonly known as motes. In the past few years, several reliable, congestion controlled and energy efficient transport layer protocols in wireless sensor networks have been developed and proposed in the literature. In this paper, we have presented a hybrid and dynamic reliable transport protocol which provides the mechanism to dynamically assign the timing parameters to the nodes as well as enhance the protocol performance by using a hybrid Acknowledgement/Negative Acknowledgement scheme. The performance of proposed protocol is tested under TinyOS Simulator varying different parameters and protocol settings and found that proposed protocol is able to program all the nodes when given proper pump/fetch ratios, is able to solve the booting sensor nodes problem by being able to wait till all the nodes finished booting and solves the all-packets-lost problem by acknowledging the receipt of its first packet delivered that is the inform message.